DEWAN DIREKSI PEREMPUAN DAN NILAI PERUSAHAAN (Bukti Empiris Dari Sektor Perbankan yang Terdaftar di BEI Tahun 2019-2023) - Putri Indriani; Poppy Nurmayanti; Hariadi Yasni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
he purpose of this study is to examine and analyze the influence of female board of directors on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The population in this study consists of banking companies listed on the IDX from 2019 to 2023, totaling 47 companies. Using a purposive sampling technique, 36 companies were selected, with a 5-year observation period, resulting in a total of 180 observational data points. The type of data used is quantitative data, sourced from secondary data obtained from company annual reports. Data collection was conducted through documentation, and data analysis was performed using multiple linear regression analysis. The results of the study indicate that the proportion of female directors has a positive effect on firm value, and the threshold effect also has a positive influence on firm value. However, the presence of female directors, as measured by the Blau Index, shows a negative effect on firm value. Keywords: Proportion of female directors, threshold, presence of female directors, firm value.